Compared study of physical activity, sedentary lifestyle and physical self-concept among chilean adolescents with and without special educational - Soler, Noemi Salvador (2022)
The objective of the study was to compare the level of physical activity (PAL), sedentary lifestyle and physical self-concept in school students of both genders in the region of Araucanía (Chile) with and without Transitory Special Educational Needs (TSEN). The research has a quantitative approach with a non-experimental, cross-sectional design and a compared descriptive scope. The assessment included 43 adolescents between 15-17 years old in the region of Araucanía, with and without TSEN. The team applied the international physical activity questionnaire (IPAQ), the physical self-concept questionnaire (CAF) and the adolescent sedentary activity questionnaire (ASAQ). The main results showed that, as related to PAL, the majority of students without TSEN were situated in the medium level, while those with TSEN were situated in the lower level with significant differences between them. Concerning the sedentary lifestyle, both groups showed a highly sedentary behavior, without significant differences and with a 3415 minute average. For physical self-concept, no significant differences were observed in the comparison. The conclusion is that, while adolescents with TSEN showed a physical self-concept and sedentary behavior similar to adolescents without TSEN, their levels of physical activity were significantly lower, so that the role of the Physical Education teacher can be key in the modification of habits in physical activity and sports in adolescents with TSEN, as well as in the organization of a higher offer of inclusive sports or physical instances.